Penerapan Sistem Informasi Pendataan Penerima Dana Program Keluarga Harapan pada Gampong Beurawe Kecamatan Kuta Alam berbasis Web GIS - Munawir Munawir; Susmanto Susmanto; Taufik Hidayat; Irhamni Irhamni; Zulfan Zulfan; Teuku Iskandar Shah; Nadia Fachriana (Jurnal Serambi Engineering, 2021)
Administratively, Gampong Beurawe is one of the villages in Kuta Alam District, Banda Aceh City. The Department of Social Affairs is in charge of collecting data and providing assistance to people in need of social welfare services. Data collection is done manually in the form of archives and files, this causes inefficiencies in space, security, time and costs. The Social Service has difficulties in conveying information on the Family Hope Program (PKH) which includes data on poor households, education data and health data, to the wider community and related parties, causing data information to be unclear. So we need an automatic data collection system to help collect data on the hopeful family program in Gampong Beurawe, Kuta Alam District. In the geographic information system itself, there are two important elements, namely Geographical Data which is used as a reference for attribute data. The design of the map that will be displayed in this application uses map info and google maps. This PKH acceptance mapping information system in Beurawe Village, Kuta Alam District, Banda Aceh City is to assist the Social Service, especially the social assistance and security department in the storage and delivery of information data (PKH) so that it can provide clear information about the program. Data information system in the form of maps, graphs and tables.